E-Coaching : theory and practice for a new online approach to coaching - Ribbers, Anne, ....-; Waringa, Alexander, ....- (London : Routledge, 2015)
In a rapidly moving world where so many of our day-to-day activities are now online, it has become essential to adapt coaching processes in order to better suit clients' circumstances and needs. Above all, clients want sustainable and time-efficient results. Electronic coaching (e-coaching) is an inevitable development for every professional who coaches, mentors, teaches, supervises, guides or helps people in their jobs. The book is underpinned by a theoretical framework that introduces a new model of people development (the ABC model), inspired by Graham Alexander's GROW model, and a new text-based coaching method inspired by Brown and Levinson's politeness theory. E-coaching is practical in its approach, with explanations on safeguarding the security and privacy of your clients, how to calculate rates, managing expectations and other important aspects of coaching online. The first English-language text available on e-coaching, this book presents a unique combined approach of method and technique, supplemented with a sample e-coaching programme. It is a must-read for all coaches, mentors, supervisors, teachers or HR professionals who want to coach in a modern way, as well as students studying on coaching courses.